Narrative Policy Analysis of Gender-Responsive Budgeting Practices in Indonesia Local Governments: The Case of Mojokerto Regency, East Java - Setya Ade Pribadi , Ayub; Fadillah Putra; Wike (Jurnal Ilmiah Administrasi Publik, 2026)
This study investigates the implementation of Gender-Responsive Budgeting (GRB) within local government development planning in Indonesia, using Mojokerto Regency as a case study. Applying Rhonda Sharp’s four-dimensional GRB framework and the Narrative Policy Framework (NPF), the research analyzes how GRB is operationalized and how policy narratives shape institutional behavior. The findings reveal that GRB has raised awareness within select agencies but remains fragmented and procedural. Key barriers include limited financial allocations, weak inter-agency coordination, superficial gender analysis, and marginalization of grassroots actors. Textual and network analyses confirm that challenges dominate stakeholder discourse, and decision-making power is concentrated in a few central institutions. The narrative elements consist of protagonists (DP2KBP2, BAPPEDA), antagonists (resistant OPDs), victims (marginalized groups), and allies (civil society) and unfold within a constrained governance setting, where the plot centers on the tension between mandates and practice. The moral emphasizes the need for leadership and reform, while belief systems reflect contested views of gender equity. The study concludes that advancing GRB requires sustained commitment, inclusive participation, and coherent policy narratives that frame gender equity as a strategic imperative